2012
DOI: 10.1159/000342039
|View full text |Cite
|
Sign up to set email alerts
|

Complete Response after Neoadjuvant Therapy in Rectal Cancer: To Operate or Not to Operate?

Abstract: Background/Aims: Evidence exists to support both surgical and nonoperative observational approaches to the management of patients with distal rectal cancer who achieve a complete response following neoadjuvant chemoradiotherapy (CRT). This article summarizes findings from key studies on management strategies for complete pathologic and clinical responders after neoadjuvant CRT for rectal cancer. Methods: A comprehensive literature review was undertaken comparing complete responders to neoadjuvant CRT who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 121 publications
0
25
0
3
Order By: Relevance
“…Of 90 patients, 23 had local recurrence only, 5 had combined systemic and local recurrence and 8 patients had only systemic recurrence. However, overall recurrence was 40 % [9,10]. Dedemadi and Wexner in a review reported excellent long-term survival in patients who had a complete clinical response after neoadjuvant CRT treated both with surgery and non-surgical management [9].…”
Section: Introductionmentioning
confidence: 99%
“…Of 90 patients, 23 had local recurrence only, 5 had combined systemic and local recurrence and 8 patients had only systemic recurrence. However, overall recurrence was 40 % [9,10]. Dedemadi and Wexner in a review reported excellent long-term survival in patients who had a complete clinical response after neoadjuvant CRT treated both with surgery and non-surgical management [9].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with rectal cancer who receive neoadjuvant CRT, rates of complete pathologic response range from 5 to 44 %, while rates of pathologic complete response of nodal disease in patients with pathologic complete response of the primary tumour range from 0 to 15 %. Given the possibility of performing "interim" metabolic and functional evaluation, experts are now beginning to debate the question of what to do in patients with a pathologic complete response also demonstrated by FDG PET/CT; it is still necessary to expose them to the rigours of aggressive surgery or would a wait-and-see strategy be more appropriate [22]? In an interesting paper, just published in the European Journal of Nuclear Medicine and Molecular Imaging, Murcia Duréndez et al stated that PET/CT is a reliable technique for assessing response to neoadjuvant radiochemotherapy (RCT) in locally advanced rectal cancer, with a view to considering more conservative surgical treatment [23].…”
Section: Neoadjuvant and Adjuvant Crt In Resectable Rectal Cancermentioning
confidence: 99%
“…From this perspective, the work of Calvo et al is worthy of attention and calls for further, SUV-based and clinically oriented investigations. We are well aware that the various problems surrounding SUVs-for example, problems in SUV calculation and reproducibility, clearly set out in the European Journal of Nuclear Medicine and Molecular Imaging editorial [22]-are still far from resolved. A partial solution to these problems, as outlined by Calvo et al in their work, could possibly lie in correct standardization of the method and the accumulation of experience, by single centres, in order to increase confidence and familiarity with imaging and its clinical implications.…”
Section: Is the Time Ripe For Suv-based Diagnostic Algorithms?mentioning
confidence: 99%
“…6,7 The capacity to predict pCR states in rectal cancers through preoperative clinical assessment thus has substantial benefit, not only in terms of prognostication but also in planning individualised therapies. 8 Unfortunately, routine clinical practices (digital rectal examinations and sigmoidoscopy) are far from satisfactory for this purpose. 1,9,10 Magnetic resonance imaging (MRI) is a valuable imaging tool that is widely utilised for local staging of rectal cancer.…”
Section: Introductionmentioning
confidence: 99%